THE FUTURE OF MANAGEMENT ACCOUNTING IN THE DIGITAL ERA: A COMPREHENSIVE LITERATURE REVIEW - Zulkifli, Zulkifli (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This paper provides a comprehensive review of the literature on the future of management accounting in the digital era. It synthesizes global studies examining how emerging technologies—including artificial intelligence (AI), big data analytics, robotic process automation (RPA), blockchain and cloud computing—are reshaping management accounting practices, roles and competency requirements. The review identifies four dominant themes: (1) the evolution of management accounting from traditional reporting toward strategic business partnering, (2) the transformative impact of digital technologies, (3) the emergence of new digital competencies, and (4) organizational and strategic implications. Across these themes, the findings indicate that the combined adoption of RPA and cloud technologies enhances operational efficiency, while blockchain offers an immutable solution to data integrity challenges inherent in Big Data processed by AI. However, scalability within cloud environments remains a key limitation. AI, supported by Big Data, enables highly personalized services, and its integration with blockchain presents opportunities for new forms of Decentralized Autonomous Organizations (DAOs). Organizational readiness varies substantially; the adoption of AI and Big Data requires cultural transformation and advanced analytical capabilities, whereas cloud implementation is primarily technical.